DEVELOPMENT OF THERMODYNAMIC RESEARCHES OF METAL ALLOYS ON PHYSICAL CHEMISTRY DEPARTMENT: UDC 541.11 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
There are described the basic results on thermodynamic properties of the liquid alloys binary and multicomponent systems of received by followers of professor G.I.Batalin, since 60th years of the last century on present time. It is shown, that constant improvement of experimental equipments has allowed to receive authentic thermodynamic properties of melts of about two hundred binary and multicomponent systems.
Keywords: -